2020
DOI: 10.1080/10810730.2020.1838003
|View full text |Cite
|
Sign up to set email alerts
|

Framing the Clinical Encounter: Shared Decision-Making, Mammography Screening, and Decision Satisfaction

Abstract: The study examines whether physicians' framing of clinical interactions is related to patient shared decision-making (SDM) satisfaction when using a clinical decision support tool (CDST) concerning mammographic screening. To answer this question, we combined (a) system log data from a CDST, (b) content coding of the physicians' message framing while using the CDST, and (c) a post-visit patient survey to assess SDM satisfaction concerning screening mammography. Results suggest that two types of message frames -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…28,30,31 We also found that primary care provider framing of risk and potential outcomes during the SDM interaction influenced patient satisfaction. 31…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…28,30,31 We also found that primary care provider framing of risk and potential outcomes during the SDM interaction influenced patient satisfaction. 31…”
Section: Resultsmentioning
confidence: 58%
“…Provider-identified barriers included not enough time for discussion although having the SDM available in the EHR helped. 28,30,31 We also found that primary care provider framing of risk and potential outcomes during the SDM interaction influenced patient satisfaction. 31 Team consensus (Table 1) revealed that TS principles varied by the PDSA cycle and phase.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…The formula defined by O'Connor calls for items to be summed, divided by 15, and multiplied by 25, such that total scores range from 0 to 100. For ease of interpretation, decisional conflict scores were reverse coded such that higher scores indicate higher satisfaction with SDM, whereas lower scores represent lower satisfaction with SDM [43].…”
Section: Survey Datamentioning
confidence: 99%